The Influence of Service Quality and Satisfaction of Outpatients of Hospital.X with The Intention to Revisit - Felisa Ayu Ananda (Eduvest - Journal of Universal Studies, 2024)
This study aims to identify the effect of service quality on outpatient satisfaction and the intensity of repeat visits at the K.R.M.T. Regional Hospital. Wongsonegoro Semarang (RSWN). Using quantitative methods and descriptive analysis, this study involved 107 outpatients selected based on inclusion and exclusion criteria. Data were collected through observation, interviews, questionnaires, and literature studies, and analyzed using validity, reliability, classical assumption tests, and T and F hypothesis tests. The results showed that service quality had a significant effect on patient satisfaction (p < 0.05), with aspects of diagnostic accuracy, staff skills, and effective communication having a positive impact. Service quality also affects the intensity of repeat visits, with an increase in service quality positively associated with the frequency of return visits. Regression test results showed 8.4% of the variation in patient satisfaction was explained by service quality. The conclusion of this study is that improving service quality can increase satisfaction and encourage repeat visits. Hospitals are advised to improve service quality through staff training, improved facilities, and better communication systems.